How Does Early Adulthood Arrest Alter Substance use Behavior? Are There Differential Effects by Race/Ethnicity and Gender? - Hassett-Walker, Connie R. (Journal of developmental and life-course criminology, 2017)
Much criminal justice research has ignored racial/ethnic and gender differences in substance use subsequent to criminal justice involvement. This paper investigated how early adulthood arrest (i.e., 18 to 21 years of age) influences individuals’ subsequent transitions from non-substance use to substance use and substance use to non-substance use through age 30. We also consider if these relationships differ by race/ethnicity and gender. Processes proscribed by labeling theory subsequent to getting arrested are considered.